HDPE and PET as Aggregate Replacement in Concrete: Life-cycle assessment, Material Development and a case study. (December 2021) - Gravina, Rebecca J.; Xie, Tianyu; Bennett, Bree; Visintin, Phillip
Abstract: This paper reports on a comprehensive research program and practical application of concrete made from recycled plastic materials for use in municipal concrete infrastructure. A systematic life-cycle analysis (LCA) is first conducted to evaluate the global warming potential of concrete containing recycled plastic waste. Using the outcomes of this analysis critical allowable plastic aggregate (PA) content which maintains mechanical properties and minimises global warming potential is identified. Using the LCA results as guidance, laboratory investigations at different scales are undertaken to develop mix designs using recycled plastic materials and to characterize the physical, mechanical and durability-related properties of the waste-based concrete products. Having developed concrete mixes that meet practical and commercial requirements, field applications of the concrete mixes as pavement materials were undertaken to demonstrate the concrete has appropriate engineering properties to enable its use in municipal infrastructure. The field demonstrations support the further development of new concretes with viable sustainable alternative materials as aggregate replacement and are expected to encourage industry and end-user take up of recycled plastic waste materials in concrete for municipal construction application. Highlights: A large-scale LCA is undertaken to assess the environmental performance of PAC Laboratory investigations at different scales are conducted to develop mix of PAC Properties of the developed PAC are experimentally studied The innovative "green" premix concrete has appropriate engineering properties Field applications of the developed concrete as pavement materials are performed